Encyclopedia of Life Sciences 2017
DOI: 10.1002/9780470015902.a0002164.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Immune Complex Diseases

Abstract: Immune complex diseases encompass a diverse group of inflammatory conditions characterised by antigen–antibody deposition and attendant activation of complement. Common manifestations include glomerulonephritis, synovitis and dermal vasculitis. Many patients present with constitutional symptoms and less specific signs. A century of research has elucidated the structure of immunoglobulin, furthered understanding of antigen–antibody‐binding interactions and yielded insights into the biochemistry and disorders of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Aside from neutralizing activity, IgG antibodies that bind to virus particles or viral antigens can form immune complexes (ICs) that may have a profound impact on disease pathogenesis, especially with regard to inflammation. This is observed in some autoimmune and infectious diseases where persistent ICs drive a hyperinflammatory response that damages host tissues ( 8 ). A clear mechanism underlying modulation of inflammation by antibodies is via IgG interactions with activating and inhibitory Fc gamma receptors (FcγRs) on myeloid cells, which are central regulators of the inflammatory response.…”
mentioning
confidence: 99%
“…Aside from neutralizing activity, IgG antibodies that bind to virus particles or viral antigens can form immune complexes (ICs) that may have a profound impact on disease pathogenesis, especially with regard to inflammation. This is observed in some autoimmune and infectious diseases where persistent ICs drive a hyperinflammatory response that damages host tissues ( 8 ). A clear mechanism underlying modulation of inflammation by antibodies is via IgG interactions with activating and inhibitory Fc gamma receptors (FcγRs) on myeloid cells, which are central regulators of the inflammatory response.…”
mentioning
confidence: 99%
“…In our study, we found elevated IL-6 and TNFa levels, and these levels increased with each treatment cycle in concordance with increased humoral immune responses. Clearly, the formation of immune complexes and downstream reactions pose a safety risk 24 . We therefore implemented a prophylactic regimen consisting of pretreatment with cyclophosphamide/Cytoxan and glucocorticoids.…”
Section: Discussionmentioning
confidence: 99%
“…Immune complex diseases, such as rheumatoid arthritis and systemic lupus erythematosus, encompass a diverse group of inflammatory conditions characterized by antigen‐antibody deposition. Typical manifestations are glomerulonephritis, synovitis, and dermal vasculitis 1 . Activation of neutrophils, resulting from the interaction with immune complexes, leads to the production of oxygen‐free radicals and the release of lysosomal enzymes, 2 which may bring about tissue inflammation and organ damage.…”
Section: Introductionmentioning
confidence: 99%